Kiat Dalam Pengelolaan Tingkat Kesehatan Bank Syariah (Studi Kasus Bank Perekonomian Rakyat Syariah Al Makmur) - Aziz, Zakaria; Prawira, Adi; Yunimar, Yunimar; Nasfi, Nasfi (El-kahfi | Jurnal Ekonomi Islam, 2023)
The discussion in this research is Tips for Managing the Health Level of Sharia Banks, the research object of PT. Al Makmur Sharia People's Economic Bank in West Sumatra financial reporting period end of December 2021-2023. The problem is that the Bank's Soundness Level is decreasing, especially the CAR, NPF and BOPO ratios. Descriptive quantitative research type and descriptive analysis method research technique. Secondary data source from the Financial Services Authority website. From financial data, it was found that the CAR position would decrease by 3.13% in 2023, as well as an increase in NPF to 1.32% and an increase in BOPO to 77.08%. Research results: Tips taken by Management to improve the bank's health level in the future, (1) increase the capital CAR ratio through additional capital from last year's profits, (2) overcome problematic financing or reduce the NPF ratio, (3) increase efficiency and reduce costs and (4) improving the internal management monitoring function.